Basic considerations in combined buoyancy-induced and forced flow in a vertical open shaft - Kim, SY; Jaluria, Y (HEMISPHERE PUBL CORP, 1998)
The laminar buoyancy and pressure-induced flow in a vertical enclosure, which models the elevator shaft of a multistoried building, has been numerically investigated to determine the underlying physical processes and mechanisms for the spread of smoke and hot gases produced by a fire. At the shaft inlet, a flow of hot gases is imposed and the walls are assumed to be adiabatic except for the ceiling, where a convective boundary condition is employed. The shaft is considered to be with or without a side vent. The effects of the important governing parameters on the flow and thermal fields are investigated in detail. Of particular interest in the study are the time taken by the flow from the inlet to the exhaust, the temperature at the exhaust, and the escape of gases through the side vent. The results obtained indicate that the hot gases flow upward over the entire cross section of the shaft when the Grashof number Or is small. However, a thin boundary layer is formed along the wall containing the inlet and exhaust channels as Or increases. The time taken by the gases from the inlet to the exhaust is analytically and numerically estimated. For a shaft with a side vent hot gases introduced at the inlet flow out through the side vent as well as the top exhaust when Gr is small. As Gr increases, however, entrainment of ambient air into the shaft occurs through the side vent. A critical Froude number beyond which the escape of hot gases through the side vent is prevented is found to vary from 0.30 to 0.81 for the parametric ranges considered in the present study.
Keywords: NATURAL-CONVECTION; WALL